2010
DOI: 10.1111/j.1463-1326.2010.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Six weeks' sebacic acid supplementation improves fasting plasma glucose, HbA1c and glucose tolerance in db/db mice

Abstract: Aim: To investigate the impact of chronic ingestion of sebacic acid (SA), a 10-carbon medium-chain dicarboxylic acid, on glycaemic control in a mouse model of type 2 diabetes (T2D).Methods: Three groups of 15 db/db mice were fed for 6 weeks either a chow diet (Ctrl) or a chow diet supplemented with 1.5 or 15% (SA1.5% and SA15%, respectively) energy from SA. Fasting glycaemia was measured once a week and HbA1c before and after supplementation. An oral glucose tolerance test (OGTT) was performed at the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…(Membrez et al . ). Consequently, SH‐SY5Y cells were exposed, in an identical manner to the incubations involving C10, to sebacic acid.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(Membrez et al . ). Consequently, SH‐SY5Y cells were exposed, in an identical manner to the incubations involving C10, to sebacic acid.…”
Section: Resultsmentioning
confidence: 97%
“…This latter process generates the dicarboxylic acid form of C10, sebacic acid, which has been shown to exhibit biological activity including improving glucose tolerance (Membrez et al . ). In contrast to such studies, sebacic acid in our experimental system showed no effect which again suggests the specificity of C10 with regards to causing mitochondrial proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…When the diet of db/db mice was supplemented with 15% of the energy deriving from sebacic acid over a period of 6 weeks, glycaemic control was significantly improved in comparison with the control group [37]. Indeed, fasting plasma glucose and glycated haemoglobin dropped to Dicarboxylic acids for type 2 diabetes values 40 and 25%, respectively, lower than in control animals (P < 0.01) and became comparable to that of lean healthy db/+ animals.…”
Section: Sebacic Acid In Diabetesmentioning
confidence: 89%
“…Higher plants, such as rye and other grains, are natural sources of dicarboxylic acids, and the increased gastrointestinal content is therefore most likely derived from the microbial fermentation of the aleurone matrix. In addition, increased urinary secretion of dicarboxylic acids has been described in response to rye rich diets. , The role of dicarboxylic acids in human nutrition remains to be elucidated in further detail; however, oral supplementation of sebacic acid in type-2 diabetic mice have been shown to improve glycemic control by increasing insulin-mediated glucose clearance and reducing fasting plasma glucose concentrations compared to control animals . An increased intake of rye resulting in increased absorption of dicarboxylic acids could therefore partly explain the beneficial effects of rye on insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%